Photometry of stars in galactic clusters - Amhed, Fazal (The University of Edinburgh, 1963)
The work is described in three main parts. Section I contains a detailed investigation of the Pleiades. The investigation is based up on star counts, published proper motions, and an extensive three -colour photometry of the Pleiades region. It is found that the dispersion of the faint members of the Pleiades at lower luminosities (Herbig 1962) is due to errors of several tenths of a magnitude in the photographically determined colours of Johnson and Mitchell (1958), and to the inclusion of field stars within the proper motion criterion. It is also established that the main sequence of the Pleiades extends as faint as V = 15ᵐ.0 and there is no evidence of a contracting sequence brighter than V = 15ᵐ.0 . An excess of red stars in the magnitude range 10 < V < 12 in the cluster area appear to be distant red giants; although these are viewed through the nebulosity, they do not appear to be significantly reddened.

Section II deals with the three -colour photometry of the southern galactic cluster NGC 3766. This work has been published. The colour excess of the cluster is Oᵐ.16 , its distance is 1450 parsecs, and its age lies in the neighbourhood of 10⁷ years.

Section III describes an investigation into the optical alignment and photometric errors of the Edinburgh Schmidt telescope.